Kawasaki disease following immunization reported to the Canadian Immunization Monitoring Program ACTive (IMPACT) from 2013 to 2018. Issue 5 (30th November 2022) - Alsager, Khaled; Khatri Vadlamudi, Nirma; Jadavji, Taj; Bettinger, Julie A.; Constantinescu, Cora; Vaudry, Wendry; Tan, Ben; Sauvé, Laura; Sadarangani, Manish; Halperin, Scott A.; Top, Karina A.
ABSTRACT: Kawasaki disease (KD) is an acute systemic vasculitis primarily affecting children younger than 5 y of age that has been reported as an adverse event following immunization (AEFI). The Canadian Immunization Monitoring Program ACTive (IMPACT) conducts active surveillance for KD following immunization across Canada. We characterized KD cases reported to IMPACT between 2013 and 2018. Cases admitted to an IMPACT hospital with a physician diagnosis of complete or incomplete KD with onset 0–42 d following vaccination were reviewed. Cases meeting the Brighton Collaboration case definition (BCCD) levels of diagnostic certainty levels 1 a/b, 2a/b or 3a-e were defined as KD cases. Demographic and vaccination characteristics were compared between KD cases and non-cases. Of 84 cases reviewed, 58 met the BCCD: 47 (81%) cases met level 1a (Complete KD), 8 (14%) met level 1b (Incomplete KD), 2 (3%) met level 2a, and 1 (2%) met level 2c (Probable KD). Median age at admission was 13 months (interquartile range 7–26 months). A median of 9.5 cases were reported per year (range 4–14). Thirty-one (53%) KD cases were temporally associated with diphtheria-tetanus acellular pertussis containing vaccinations, followed by 21 (36%) cases with pneumococcal conjugate vaccines. Symptom onset was 0–14 d after vaccination in 32 (55%) cases. Echocardiogram results were available for 43 (74%) cases with 22 reported as abnormal. Age, sex, interval to symptom onset, and vaccines received were similar between KD cases and non-cases. No safety signals were detected in these data.